The Ultimate Depression Survival Guide : Protect Your Savings, boost Your Income, and Grow Wealthy Even in the Worst of Times - Weiss, Martin D. (Hoboken John Wiley, 2009)
Having an effective financial and personal plan for the future is now more crucial than ever. And with The Ultimate Depression Survival Guide, readers will quickly learn how to create such a plan. This comprehensive guide was especially designed to help people map out a practical financial plan in this unpredictable economic environment, so that they can stop worrying about their money and just enjoy life. Step by step, Martin Weiss--America's Consumer Advocate for Financial Safety--introduces, explains, and helps solve many of the new challenges and risks that face millions of Americans.
Include Index and Notes
Keywords: United States -- Financial crises -- Investment analysis